Pediatric Long-Term Endotracheal Intubation and Role for Tracheostomy: Patient and Provider Factors - Ackerman, Kassi; Saley, Taylor P.; Mushtaq, Nasir; Carroll, Timothy (Journal of Pediatric Intensive Care, 2019)
Tracheostomy provides an alternative to long-term intubation in patients with respiratory failure, but there is little guidance for its use in pediatric patients. Our study used provider surveys of pediatric intensive care physicians managing patients intubated longer than 14 days to evaluate accuracy of physician estimates for total intubation time and the impact of medical history and illness category on determining tracheostomy placement. Providers' ability to estimate length of intubation was found to be highly inaccurate. With delayed tracheostomy conferring increased risk and mortality, better recommendations regarding indication and timing of pediatric tracheostomy placement are needed.
Keywords: pediatric; tracheostomy; intubation